1,800 MHz Radiofrequency Electromagnetic Irradiation Impairs Neurite Outgrowth With a Decrease in Rap1-GTP in Primary Mouse Hippocampal Neurons and Neuro2a Cells - Li, Yanqi; Deng, Ping; Chen, Chunhai; Ma, Qinlong; Pi, Huifeng; He, Mindi; Lu, Yonghui; Gao, Peng; Zhou, Chao; He, Zhixin; Zhang, Yanwen; Yu, Zhengping; et al. (Frontiers in Public Health, 2021)
Background: With the global popularity of communication devices such as mobile phones, there are increasing concerns regarding the effect of radiofrequency electromagnetic radiation (RF-EMR) on the brain, one of the most important organs sensitive to RF-EMR exposure at 1800 MHz. However, the effects of RF-EMR exposure on neuronal cells are unclear. Neurite outgrowth plays a critical role in brain development, therefore, determining the effects of 1800 MHz RF-EMR exposure on neurite outgrowth is important for exploring its effects on brain development. Objectives: We aimed to investigate the effects of 1800 MHz RF-EMR exposure for 48 hours on neurite outgrowth in neuronal cells and to explore the associated role of the Rap1 signaling pathway. Material and methods: Primary hippocampal neurons from C57BL/6 mice and Neuro2a cells were exposed to 1800 MHz RF-EMR at a specific absorption rate (SAR) value of 4 W/kg for 48 hours. CCK-8 assays were used to determine the cell viability after 24, 48 and 72 hours of irradiation. Neurite outgrowth of primary hippocampal neurons (DIV 2) and Neuro2a cells was observed with a 20× optical microscope and recognized by ImageJ software. Rap1a and Rap1b gene expressions were detected by real-time quantitative PCR. Rap1, Rap1a, Rap1b, Rap1GAP, and p-MEK1/2 protein expressions were detected by western blot. Rap1-GTP expression was detected by immunoprecipitation. The role of Rap1-GTP was assessed by transfecting a constitutively active mutant plasmid (Rap1-Gly_Val-GFP) into Neuro2a cells. Results: Exposure to 1800 MHz RF-EMR for 24, 48 and 72 hours at 4 W/kg did not influence cell viability. The neurite length, primary and secondary neurite numbers, and branch points of primary mouse hippocampal neurons were significantly impaired by 48-hour RF-EMR exposure. The neurite-bearing cell percentage and neurite length of Neuro2a cells were also inhibited by 48-hour RF-EMR exposure. Rap1 activity was inhibited by 48-hour RF-EMR with no detectable alteration in either gene or protein expression of Rap1. The protein expression of Rap1GAP increased after 48-hour RF-EMR exposure, while the expression of p-MEK1/2 protein decreased.